DAMPAK UNDANG-UNDANG REPUBLIK INDONESIA NO.11 TAHUN 2016 TENTANG PENGAMPUNAN PAJAK TERHADAP KONDISI BURSA EFEK INDONESIA - Sumadi, Magna Mayputra; Wiagustini, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to analyze the difference of the mean significance of abnormal return before and after the event and to test the market reaction due to the tax amnesty event. This research uses a sample of 34 stocks of LQ45 in Indonesia Stock Exchange by using purposive sampling sampling method. This research is done by method of event study study with Market Adjusted Model. The period of the event examined for each event is 15 trading days, ie seven days before the event, one day at the time of the event and seven days after the event. The statistical tests were performed to compare average abnormal returns before and after events and to see market reactions around the event. The result of the research shows that there is no difference of average abnormal return before and after the event of tax amnesty policy, the end of the tax amnesty period I, the end of the tax amnesty period II and the end of the tax amnesty period III. There is no market reaction around the event of the tax amnesty policy, but there is market reaction in the event of the end of the tax amnesty period I, the event of the end of the second amnesty tax period and the end of the tax amnesty period III. The end of the tax amnesty period I, II and III contain information.